PELAKSANAAN PROGRAM PENINGKATAN PERANAN WANITA DI JAWA TIMUR - Wijaya, Hesti R. (Jurnal Bestari, 1994)
In the era of development at present, women's participation. in development program is sti little. Women with this biological existence are placed at ine rank less than men are. Consequently, a number of women have lead life conditions.